Character Strengthening through Routine School Practices: Design Models from a Systematic Review - Pujiastuti, Lusi Andri; Hitta, Hitta Alfi Muhimmah; Ummah, Fiena Saadatul (Universitas Pendidikan Mandalika, 2026)
This study aims to identify effective models, implementation strategies, and instructional design principles for routine-based character strengthening programs in elementary schools. A qualitative systematic literature review was conducted following PRISMA guidelines. A total of 24 peer-reviewed articles published between 2022 and 2025 were collected primarily from the Scopus database. Data were analyzed using thematic synthesis through a structured extraction matrix encompassing intervention design, routine practices, targeted character values, implementation strategies, and outcomes. The findings reveal that effective character education models integrate four core components: value-based learning through daily routines, teacher exemplarity and collaboration, a conducive school environment and culture, and holistic curriculum integration. Prominent models identified include Lickona’s comprehensive approach, the R2SC technique (Routine, Role Model, Spontaneity, Conditioning), the TRECB model (Transformative Reflexive Empowering Character Building), and ethnopedagogical frameworks incorporating local wisdom. Routine activities such as morning prayers, flag ceremonies, classroom duties, 5S culture (Smile, Greet, Polite, Courteous, Honest), and honesty journals were found to be effective in instilling core character values. Challenges remain in teacher training, character assessment systems, model standardization, and cross-cultural adaptation. The review recommends strengthening the educational ecosystem through comprehensive teacher professional development, innovative learning modules, continuous evaluation mechanisms, and school-family-community collaboration. These findings provide practical guidance for educators, policymakers, and researchers in designing sustainable, routine-based character education programs in elementary schools. This review advances the field by synthesizing a framework that supports the transition of character education from isolated classroom instruction to embedded, school-wide cultural practices.